A Survey On Effective Factors On Knowledge Management From The Perspective Of University Librarians In Urmia - Abbas Doulani; Mohammad Jabraeily Mazrae Sadi; Bohlul Rahimi; Ali Rashidi (Tehran University of Medical Sciences, 2013)
Background and Aim: Knowledge management is effective in promoting organizational structure, level of services, and universities competency power. The present study was aimed to assess knowledge management effective factors including information technology, organization culture, human resources, and librarians' skills among university librarians in Urmia. Materials and Methods: This analytical survey was conducted on 102 university librarians in Urmia. The data were collected using a questionnaire where its validity and reliability was confirmed by specialists' overviews and Cronbach's Alpha (0.94). In order to analyze the data, first the middle of the effective factors of knowledge management was estimated. Next, synchronic effect of the variables was estimated via multinomial logistic regression. Also Chi-square was used to assess the relationship between majors and sex factor of the librarians considering their perspective on knowledge management. Results: Organizational culture, information technology and human resources are the most effective factors to knowledge management circulation. Also the median degree of the knowledge management process includes knowledge creation and reservation and knowledge sharing and employing; which was 2/7 and 2/2 respectively. Conclusion: Knowledge management is an important factor in human resources and competency environment of organizations. Libraries can with launching of knowledge management circulation, earn some promotions, for example: saving research and development costs, capacity increasing, employers' job satisfaction, maintenance of competency environment and etc.